Quantitative microscopy of high temperature materials - Strang, A.; Cawley, J. (IOM Communications Ltd., 2001)
The fifth in the series of international conferences on High Temperature Materials, the papers in this volume cover the processing and properties of Ti alloys for automotive, aerospace, and other high temperature applications.
"5th of the Institute of Materials' series of international conferences on the microstructure of high temperature materials and second to be held at the Material Research Institute of Sheffield Hallam University"--Foreword.
Keywords: Materials -- Creep -- Congresses.; Microstructure -- Congresses.; Materials at high temperatures -- Congresses.; Microscopy -- Technique -- Congresses.; elektronické knihy; electronic books